A prospective, observational study of fidaxomicin use for Clostridioides difficile infection in France. Issue 6 (June 2021) - Guery, Benoit; Berger, Pierre; Gauzit, Remy; Gourdon, Magali; Barbut, Frédéric; ,; DAFNE study group:,; Bémer, Pascale; Bessède, Emilie; Camou, Fabrice; Cattoir, Vincent; Couzigou, Carine; et al.
Objective: To describe the characteristics, management and outcomes of hospitalised patients with Clostridioides difficile infection (CDI) treated with and without fidaxomicin. Methods: This prospective, multicentre, observational study (DAFNE) enrolled hospitalised patients with CDI, including 294 patients treated with fidaxomicin (outcomes recorded over a 3-month period) and 150 patients treated with other CDI therapies during three 1-month periods. The primary endpoint was baseline and CDI characteristics of fidaxomicin-treated patients. Results: At baseline, the fidaxomicin-treated population included immunocompromised patients (39.1%) and patients with severe (59.2%) and recurrent (36.4%) CDI. Fidaxomicin was associated with a high rate of clinical cure (92.2%) and low CDI recurrence (16.3% within 3 months). Clinical cure rates were ≥90% in patients aged ≥65 years, those receiving concomitant antibiotics and those with prior or severe CDI. There were 121/296 (40.9%) patients with adverse events (AEs), 5.4% with fidaxomicin-related AEs and 1.0% with serious fidaxomicin-related AEs. No fidaxomicin-related deaths were reported. Conclusions: Fidaxomicin is an effective and well-tolerated CDI treatment in a real-world setting in France, which included patients at high risk of adverse outcomes. Trial registration: Description of the use of fidaxomicin in hospitalised patients with documented Clostridium difficile infection and the management of these patients (DAFNE), NCT02214771, www.ClinicalTrials.gov.